PRE-SERVICE TEACHER EDUCATION REFORMS IN INDIA AND PAKISTAN: CHALLENGES AND POSSIBILITIES - Sharma, Jyoti (International Journal of Research -GRANTHAALAYAH, 2014)
India and Pakistan are two strategically important neighboring countries in Asia-Pacific region. Since independence of more than six decades, both, India and Pakistan have transverse different paths, India as a Sovereign, Democratic, Republic Country and Pakistan as Islamic Republic of Pakistan. The advent of democracy in India and Islamic republic in Pakistan resulted in new hopes, aspirations and demands on education. During the six decades after Independence, teacher education in both countries has come a long way from its initial bleak stature to gain an identity as a complex network of institutions and programs. The present paper takes a close look into the paradigm shift in teacher education programs in India and Pakistan and how much the shift is influenced by constitutional frameworks of each country. Paper looks into the pertinent issues in pre-service teacher education such as pedagogical beliefs, theory-practice gaps, curriculum and assessment within the educational framework of both the countries. The paper identifies crucial areas that demands attention of academia of both the countries to develop research partnerships and strengthen cooperation to improvise status of “Education” as a whole in South –Asian region.